Pearl Mussel Population Dynamics in Estonia: A Study on the Interplay of Geology, Geomorphology, and Watershed Land Use - Katrin Kaldma; Marko Kohv; Tiit Hang; Joosep Aia; Argo Jõeleht; Raul Paat; Martin Kesler (Diversity)
Freshwater pearl mussels (Margaritifera margaritifera) are vital bioindicators in river ecosystems, with their population health reflecting broader environmental conditions. Mussel population declines are well documented across Europe, and in Estonia, Pudisoo River supports the last remaining population. Long-term monitoring also indicates a significant decline in Pudisoo River, but the causes remain underexplored. This study aimed to assess how geology, geomorphology, and land use changes could impact pearl mussel population trends and distribution. We conducted field surveys, bioindication tests, and hydrological and morphometric analyses to evaluate physicochemical and environmental parameters in the Pudisoo River. The study revealed a declining but stabilizing population, concentrated in river sections with higher gradients and coarser riverbed substrates. Sediment transport and accumulation, influenced by both natural and human-induced factors, significantly affect habitat suitability, especially for juvenile mussels. Positive correlations were found between mussel populations and river sinuosity, suggesting that the varied microhabitats created by sinuosity, such as gradients in flow velocity and sediment deposition, play an important role in supporting the species. This finding highlights the importance of directing in-channel restoration efforts towards enhancing channel morphology to create more diverse habitats. Research on sediment dynamics and hydrological connectivity will be crucial for developing effective habitat management strategies for the species, especially considering the impacts of land use and climate change.